Regional banks and market power: evidence from Indonesia. (2018) - Trinugroho, Irwan; ,; Damayanti, Sylviana Maya; Wiryono, Sudarso Kaderi; Nugroho, Linggar Ikhsan
This paper investigates market power difference between regional banks and other banks in the context of Indonesia over the period of 2001-2009 resulting in 641 observations. Further, we also examine the determinants of market power of regional banks by considering local institutional development. According to the univariate and multivariate tests, we do find that Indonesian regional banks have a larger market power than other commercial banks. However, contrary to our expectation, in the regions with poor governance, market power of those banks is lower than that of well-governed regions. Similarly, socio-economic development is positively linked to the market power of regional banks.